Technical mishandles occurring in building renovation and modernization = Błędy techniczne występujące przy remontach i modernizacjach obiektów budowlanych - Runkiewicz, Leonard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents current technical requirements related to adaptations, extentions and modernizations of building facilities according to the binding legal and technical documents. It also presents the technical reasons that affect the reliability and durability of repairs and modernizations which occur at the designing and the execution stages.
Keywords: obiekty budowlane; remonty; modernizacja; adaptacja; buildings; repairs; refurbishment; modernisation; adaptation